Steel-concrete composite floor systems with different structural and loading configurations under a corner column removal scenario: experimental tests - Fu, Qiu Ni (2022)
In this study, quasi-static tests were performed on three 3D steel–concrete composite floor systems under a column removal scenario with two variables, i.e., secondary beam connection type and pre-existing axial loads on columns. The work focused on the behavior of the three composite floor systems, including the load–deflection response, failure mode, load-resisting mechanism, e.g., flexure, catenary action and tensile membrane action (TMA), and load redistribution. It was found that secondary beam connection had a pronounced effect on the load–deflection response. Pre-existing axial loads on columns significantly influenced the load redistribution process and intensified the stresses in adjacent columns connected by the secondary beam to the removed column. For all the three specimens, a peripheral compressive ring with TMA was not observed in the composite slab due to a lack of rotational restraint from the perimeter beams and the main girder. However, at large deformation stage, when the composite slab deformed into an approximate hyperbolic-parabolic surface, the entire reinforcing mesh in the slab was in tension. It was observed that, at the early stage, the applied load was mainly resisted by flexure in the slab and the main composite girder and the secondary composite beam connecting to the removed column. But at large deformation stage, part of the applied load was resisted by flexure in the partially damaged slab and the main girder, and the intact secondary beam. Other load-carrying contributions came from catenary action in the main girder and TMA in the slab. In the end, most of the applied loads were redistributed to the columns adjacent to the removed column.